2018
DOI: 10.1002/jbm.b.34070
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of melanocyte transplantation by chitosan‐based melanocyte spheroid patch to skin prepared by controlled sunburn blistering

Abstract: Transplantation of autologous cultured melanocytes as cell suspension has been used for the treatment of vitiligo. The recipient site is often prepared by laser-mediated dermabrasion. Such procedures encounter disadvantages including prolonged transplantation duration, unsecured cell adherence to lesional skin and potential scarring. To improve this, here we propose a method by preparing recipient sites before transplantation by psoralen and ultraviolet A (PUVA)-induced sunburn followed by transplanting cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Many factors impair the viability of MCs transplanted in cell suspensions, including: 5,6 (1) Before transplantation, preparation of the cell suspension using trypsin digestion and mechanical shaking may damage MCs and cause them to undergo apoptosis or death. (2) During the transplantation process, it cannot be ensured that MCs in the suspension will adhere tightly to the recipient area, especially when the surface of that area is uneven.…”
Section: Disadvantages Of Cell Suspension Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…Many factors impair the viability of MCs transplanted in cell suspensions, including: 5,6 (1) Before transplantation, preparation of the cell suspension using trypsin digestion and mechanical shaking may damage MCs and cause them to undergo apoptosis or death. (2) During the transplantation process, it cannot be ensured that MCs in the suspension will adhere tightly to the recipient area, especially when the surface of that area is uneven.…”
Section: Disadvantages Of Cell Suspension Transplantationmentioning
confidence: 99%
“…It has been reported that MCs within MPs were successfully transferred to the depigmented areas of nude mice and survived well. 5 MPs were transplanted onto the epidermal wounds of nude mice and were active.…”
Section: Advantages Of Mp Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan is a deacetylated form of the invertebrate exoskeleton biopolymer, chitin, which displays many promising characteristics that include its compatibility with other natural materials used for bone tissue engineering. [118][119][120][121] Chitosan-based delivery systems seeded with bone morphogenetic protein (BMP)-2 demonstrated increases in osteocalcin synthesis in cultured human embryonic palatal cells. 122,123 More recently, hydrophobically modified glycol chitosan nanocontrolled delivery of trichloroacetic acid and epidermal growth factor in vivo in critical-sized defects in palatal soft tissues in a canine model, demonstrating successful regeneration of these palatal defects.…”
Section: Demineralized Bone Matrixmentioning
confidence: 99%
“…Among these, cell spheroid is a technology in which cells are cultured in suspension to create a 3D structure using cell-cell interactions and "scaffold-free" strategy ( Figure 8B). This technique yields detailed information regarding ECM remodeling through "omics" analysis since the generation, growth, and fusion of cells allow accurate monitoring (Fan et al, 2018;Schnellmann et al, 2018;Wong et al, 2018). Understanding the ECM and its soluble factors are essential to comprehend embryonic development and tissue repair and will contribute to the discovery of new therapeutic tools.…”
Section: New Approaches To Studying Palatogenesis and Cl/p In Vitromentioning
confidence: 99%